2007
DOI: 10.4269/ajtmh.2007.76.732
|View full text |Cite
|
Sign up to set email alerts
|

Low Efficacy of Mebendazole Against Hookworm in Vietnam: Two Randomized Controlled Trials

Abstract: Vietnam is participating in a global de-worming effort that aims to treat 650 million school children regularly by 2010. The treatment used in Vietnam is single dose oral mebendazole (Phardazone) 500 mg. We tested the efficacy of single dose mebendazole 500 mg in the therapy of hookworm infection in a randomized double-blind placebo-controlled trial among 271 Vietnamese schoolchildren. The treatment efficacy of single dose mebendazole in children did not differ significantly from placebo, with a reduction in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 29 publications
5
69
0
Order By: Relevance
“…8 The possibility of benzimidazole resistance having arisen in human hookworms has been recently reviewed, 12 but there is still no indisputable evidence, although the efficacy of mebendazole in particular has been shown to have declined in some parts of the tropics, notably in Zanzibar, Vietnam, and Mali and instances of failure with albendazole have also been reported in Ghana. [13][14][15][16] Another trend in the current analysis worth commenting on was the age-related increase in the prevalence of B. hominis ( Figure 4B), which was much like that we reported earlier 2 and hence largely unaffected after the addition of data from the three most recent years. Because these data generate some concern over B. hominis infections among the elderly, we also compared data for the first period with the second and we found that there was an overall reduction in all age groups and the upward drift in prevalence was now only evident in the very oldest age class.…”
Section: Resultssupporting
confidence: 53%
“…8 The possibility of benzimidazole resistance having arisen in human hookworms has been recently reviewed, 12 but there is still no indisputable evidence, although the efficacy of mebendazole in particular has been shown to have declined in some parts of the tropics, notably in Zanzibar, Vietnam, and Mali and instances of failure with albendazole have also been reported in Ghana. [13][14][15][16] Another trend in the current analysis worth commenting on was the age-related increase in the prevalence of B. hominis ( Figure 4B), which was much like that we reported earlier 2 and hence largely unaffected after the addition of data from the three most recent years. Because these data generate some concern over B. hominis infections among the elderly, we also compared data for the first period with the second and we found that there was an overall reduction in all age groups and the upward drift in prevalence was now only evident in the very oldest age class.…”
Section: Resultssupporting
confidence: 53%
“…However, increasing treatment failure rates with pyrantel pamoate and mebendazole have resulted in these drugs no longer being recommended for the treatment of human hookworm infection. 16,84,85 Moreover, reduced in vitro activity of mebendazole has been observed in human hookworm isolates from Pemba Island, an endemic area known for high rates of treatment failure, 86 compelling evidence of emerging resistance. Preliminary analysis of a 2010 follow-up study in Kintampo North points to an albendazole treatment failure rate of greater than 50% (Humphries D and others, unpublished observation), confirming the data reported here and raising further doubts about the effectiveness of this agent for the treatment of hookworm in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…During the past 10 years, there has been some suggestion of BZ selection occurring in filarial nematodes, 27 human hookworms, 17,22 and in human whipworms. 21 However, in these studies evidence of genetic selection was not directly linked with resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested an emergence of drug resistance by reporting low cure rates and fecal egg count reductions. 9,16,17 However, these major indicators, used for assessing drug efficacy, lack sufficient precision and accuracy to conclude the development of resistance. [18][19][20] Thus, there is an urgent need to develop better diagnostic tools for detecting BZ resistance in human parasites.…”
Section: Introductionmentioning
confidence: 99%